Preparation and Characterization of Ni/H-ZSM-5 Catalysts for Producing Green Diesel from Palmitic Acid - Kurniati, Sayekti; Azis, Muhammad Mufti; Dwiatmoko, Adid Adep (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Biofuel is a promising alternative as a sustainable energy resource in the transportation sector in Indonesia. Green diesel is one of biofuels that can be produced from feedstock containing fatty acid. Fatty acid conversion to green diesel can be conducted via hydrodecarboxylation or hydrodeoxygenation process. Catalyst Ni/H-ZSM-5 is a potential catalyst to convert fatty acid to n-alkane which is the main component in green diesel. In this work, we prepared Ni/H-ZSM-5 catalyst with various Ni loading of 7%, 13%, 18%, and 25%, respectively. The catalysts were synthesized according to a simple incipient wetness impregnation method. Those catalysts were characterized with X-ray fluorescence, Field-Emission Scanning Electron Microscopy, and NH3-TPD. The highest nickel-loading catalyst, Ni 25%/H-ZSM-5, gave the best dispersion. NH3-TPD results showed the presence of two acid sites, namely Brønsted acid site and Lewis acid site. The presence of Brønsted acid sites is crucial to facilitate fatty acid conversion to n-alkane.